Best Science Fiction of the Year. Volume 2 - Neil Clarke, ed (Night Shade Books, 2017)
To keep up-to-date with the most buzzworthy and cutting-edge science fiction requires sifting through countless magazines, e-zines, websites, blogs, original anthologies, single-author collections, and more--a task accomplishable by only the most determined and voracious readers. For everyone else, Night Shade Books is proud to introduce the latest volume of The Best Science Fiction of the Year, a new yearly anthology compiled by Hugo and World Fantasy award-winning editor Neil Clarke, collecting the finest that the genre has to offer, from the biggest names in the field to the most exciting new writers. The best science fiction scrutinizes our culture and politics, examines the limits of the human condition, and zooms across galaxies at faster-than-light speeds, moving from the very near future to the far-flung worlds of tomorrow in the space of a single sentence. Clarke, publisher and editor in chief of the acclaimed and award-winning magazine Clarkesworld, has selected the short science fiction (and only science fiction) best representing the previous year's writing, showcasing the talent, variety, and awesome "sensawunda" that the genre has to offer.